# 6(n-3)=4(n+2.1) - math

by scott
(buffalo,ny)

Simplify the following equation.

Apply the Distributive Law to eliminate the parentheses on each side of the equal sign.

6(n-3)=4(n+2.1)

### Comments for 6(n-3)=4(n+2.1) - math

 Nov 07, 2010 Solve Equation with 1 Variable by: Staff The question: by Scott (Buffalo, NY) 6(n – 3) = 4(n + 2.1) The answer: 6(n – 3) = 4(n + 2.1) Simplify the equation using the Distributive Law. Applying the Distributive Law will eliminate the parentheses on each side of the equal sign. 6 * n – 6 * 3 = 4 * n + 4 * 2.1 6n – 18 = 4n + 8.4 Group all the unknowns on one side of the equation. It does not matter which side of the equation you choose. In this example I am going to group the unknowns on the left side by subtracting 4n from each side of the equation. 6n – 4n – 18 = 4n – 4n + 8.4 2n – 18 = 0 + 8.4 2n – 18 = 8.4 Eliminate the – 18 from the left side of the equation by adding + 18 to each side. 2n – 18 + 18 = 8.4 + 18 2n + 0 = 26.4 2n = 26.4 Eliminate the 2 from the left side of the equation by dividing each side of the equation by 2. 2n = 26.4 2n/2 = 26.4/2 n = 13.2 The final answer: n = 13.2 Check your work. Substitute the number 13.2 for every n in the original equation: 6(n – 3) = 4(n + 2.1) 6(13.2 – 3) = 4(13.2 + 2.1) 6(10.2) = 4(15.3) 61.2 = 61.2 Since the equation is in balance (61.2 = 61.2), the solution of n = 13.2 is correct. Thanks for writing. Staff www.solving-math-problems.com

Join in and write your own page! It's easy to do. How? Simply click here to return to Math Questions & Comments - 01.